2006
DOI: 10.1021/jf061646z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Lactosylation of Whey Proteins by Liquid Chromatography−Mass Spectrometry

Abstract: Heat treatment of milk induces a reaction between the milk proteins and lactose, resulting in lactosylated protein species. The lactosylation of the two major whey proteins alpha-lactalbumin and beta-lactoglobulin was investigated by reversed phase liquid chromatography-mass spectrometry (LC-MS). Three sample series, consisting of aqueous model solutions of each whey protein separately and in mixture and whole milk, were heated for different time periods, and the progression of the lactosylation reaction was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 26 publications
7
42
0
2
Order By: Relevance
“…β-Lactoglobulin (β-LGB) and α-lactalbumin (α-LAB) have been identified as main protein reaction targets in dairy products [22]. Their quantitative lactosylation, generally assessed by various MS procedures, has been widely used to monitor milk quality and thermal history [22][23][24][25][26][27][28][29][30][31]; for example, it has been demonstrated that the lactosylated protein forms account for almost 3, 30 and 70% of the β-LGB content in pasteurized, UHT and dry infant formula samples, respectively. Caseins (CSNs) have also been reported as lactosylated species depending on milk thermal treatment [32].…”
Section: Introductionmentioning
confidence: 99%
“…β-Lactoglobulin (β-LGB) and α-lactalbumin (α-LAB) have been identified as main protein reaction targets in dairy products [22]. Their quantitative lactosylation, generally assessed by various MS procedures, has been widely used to monitor milk quality and thermal history [22][23][24][25][26][27][28][29][30][31]; for example, it has been demonstrated that the lactosylated protein forms account for almost 3, 30 and 70% of the β-LGB content in pasteurized, UHT and dry infant formula samples, respectively. Caseins (CSNs) have also been reported as lactosylated species depending on milk thermal treatment [32].…”
Section: Introductionmentioning
confidence: 99%
“…Additional analysis by mass spectrometry suggested the increases in mass for the whey protein peaks were approximately multiples of 320 Da consistent with incremental lactosylation reactions. Other studies have demonstrated that lactosylation of -lactoglobulin can proceed under relatively mild conditions in the absence of browning is site specific (appearing to prefer Lys 47 ), and results in conformational changes and ultimately aggregation via non-covalent interactions (Leonil et al, 1997;Morgan et al, 1999b;Chevalier et al, 2002;French et al, 2002;Czerwenka et al, 2006).…”
Section: Milk Protein Allergymentioning
confidence: 99%
“…Alternatively, a number or polyclonal and monoclonal antibodies against lactulosamine-modified proteins and polylysine have been developed, which dramatically increased sensitivity of LA analysis by the use of immunodetection techniques (78)(79)(80). More recently, efforts to develop direct instrumental analysis methods for determining lactulosamine modification in dairy products have succeeded in applying the liquid chromatographyÀmass spectrometry to enzymatic hydrolyzates of milk proteins (81,82).…”
Section: Structure Origin and Analysis In Dairy Productsmentioning
confidence: 99%